Herbivoría en cícadas (Cycadophyta) por adultos de Janbechynea elongata Jacoby, 1888 (Coleoptera: Orsodacnidae) en el ANP sierra de Otontepec, Veracruz - Reyes-Ortiz, José Luis; Luna-Ferrer, Jose Manuel; González-Gándara, Carlos; Cruz-Morales, Gerardo Eliseo; Domínguez-Barradas, Consuelo (Instituto de Ecología, A.C., 2016)
Little is known about the relationship between cycads and J. elongata. Since June 2009, adults J. elongata were observed feeding on Ceratozamia huastecorum in the Sierra de Otontepec; Cycas revoluta and C. circinalis in public and private gardens in three locations in northern Veracruz. Its arrival is sudden and occurs at the end of spring. It presents gregarious or solitary behavior. It feeds on the leaflets with smooth texture and sometimes the rachis. Large populations of adult J. elongata occur in the morning and have been removed by the inhabitants to avoid damage to their cycads, this has disrupted the careful observation of their behavior and the possible meeting of larvae, pupae and eggs. Only 5 % of the population C. huastecorum has been affected, while big Cycas revoluta and C. circinalis have been infested to 100 %.